2012
DOI: 10.1007/s11738-012-0967-1
|View full text |Cite
|
Sign up to set email alerts
|

Internal standards for quantitative RT-PCR studies of gene expression under drought treatment in barley (Hordeum vulgare L.): the effects of developmental stage and leaf age

Abstract: Drought is the most significant abiotic stress in agriculture; thus, this area of studies seems to be one of the most important challenges in plant biology. Data about gene expression under drought are crucial to study drought response mechanisms and to select the genes for a transgenic approach. Quantitative RT-PCR is a powerful method for gene expression analysis; however, obtaining proper data normalization requires internal reference genes with stable level of expression. In the present paper ten potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 40 publications
5
43
1
4
Order By: Relevance
“…Expression values were normalised against the ADP-ribosylation factor gene, which according to geNorm PLUS analysis (data not shown), displayed the highest stability of expression level. It was also suggested as the most suitable to study drought-induced changes in gene expression at the seedling stage in barley (Rapacz et al 2012). Expression values were calculated using the 2 −ΔΔCT method (Schmittgen and Livak 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Expression values were normalised against the ADP-ribosylation factor gene, which according to geNorm PLUS analysis (data not shown), displayed the highest stability of expression level. It was also suggested as the most suitable to study drought-induced changes in gene expression at the seedling stage in barley (Rapacz et al 2012). Expression values were calculated using the 2 −ΔΔCT method (Schmittgen and Livak 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Each real-time PCR reaction was performed independently for three biological replicates, and for every biological replicate three (splicing isoforms analysis) or two (pri-miRNA abundance analysis) technical replicates were performed. The barley ADP-ribosylation factor 1-like [GenBank: AJ508228.2] gene fragment of 61 nt was simultaneously amplified and detected as an internal reference [77]. Expression levels were calculated with the relative quantification method (2 -ΔCt ) as fold-change value and presented in a form of log 10 2 -ΔCt .…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was quantified using the Experion TM RNA StdSens microcapillary chip (Bio-Rad, Mississauga, ON, Canada) and its integrity based on the RNA quality indicator (RQI) calculated by the Experion TM software was always greater than 8. First-strand cDNA was synthesized from 1 µg of total RNA and oligo(dT) 18 primers using the Transcriptor First Strand cDNA synthesis Kit (Roche Applied Science, Laval, QC, Canada) following the manufacturer instructions. Any residual genomic DNA was removed by a treatment with DNaseI (Invitrogen, Burlington, ON, Canada) prior to cDNA synthesis.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…Act has been previously shown to be unstable under various experimental conditions and was deemed unsuitable to normalize stress-induced gene expression in several species [12] [21] [32] including alfalfa [30]. Rapacz et al [18] concluded that the stability of Act in barley (Hordeum vulgare) exposed to abiotic stress could depend on the developmental stage. Tub is another gene commonly used for normalization of gene expression that has been frequently shown to be unstable across species and experimental treatments [9] [12] [16] [20] [30].…”
Section: Stability Of the Expression Of Candidate Reference Genesmentioning
confidence: 99%